Large-scale mutational analysis in the EXT1 and EXT2 genes for Japanese patients with multiple osteochondromas. Issue 1 (December 2016) - Ishimaru, Daichi; Gotoh, Masanori; Takayama, Shinichiro; Kosaki, Rika; Matsumoto, Yoshihiro; Narimatsu, Hisashi; Sato, Takashi; Kimata, Koji; Akiyama, Haruhiko; Shimizu, Katsuji; Matsumoto, Kazu
Abstract Background Multiple osteochondroma (MO) is an autosomal dominant skeletal disorder characterized by the formation of multiple osteochondromas, and exostosin-1 (EXT1 ) and exostosin-2 (EXT2 ) are major causative genes in MO. In this study, we evaluated the genetic backgrounds and mutational patterns in Japanese families with MO. Results We evaluated 112 patients in 71 families with MO. Genomic DNA was isolated from peripheral blood leucocytes. The exons and exon/intron junctions ofEXT1 andEXT2 were directly sequenced after PCR amplification. Fifty-two mutations in 47 families with MO in eitherEXT1 orEXT2, and 42.3 % (22/52) of mutations were novel mutations. Twenty-nine families (40.8 %) had mutations inEXT1, and 15 families (21.1 %) had mutations inEXT2 . Interestingly, three families (4.2 %) had mutations in bothEXT1 andEXT2 . Twenty-four families (33.8 %) did not exhibit mutations in eitherEXT1 orEXT2 . With regard to the types of mutations identified, 59.6 % of mutations were inactivating mutations, and 38.5 % of mutations were missense mutations. Conclusions We found that the prevalence ofEXT1 mutations was greater than that ofEXT2 mutations in Japanese MO families. Additionally, we identified 22 novelEXT1 andEXT2 mutations in this Japanese MO cohort. This study represents the variety of genotype in MO.